No room at the top? The glass wall for professional services managers in pre-1992 English universities. (2nd October 2017) - Shepherd, Sue
ABSTRACT: Pre-1992 English universities are changing the way they appoint their deputy and pro-vice-chancellors (PVCs). Traditionally, PVC posts were filled by internal secondment from within the professoriate, but these days an increasing number are appointed by means of external open competition involving advertisement and/or executive search. So has this 'opening up' of PVC positions created new career progression opportunities for professional services managers? Findings from a census, online survey and interviews with a range of senior university managers suggest not. Despite the PVC role becoming more managerial, those getting the jobs remain overwhelmingly career academics. Professional services managers confront a glass wall, excluded from consideration by a non-negotiable requirement for academic credibility. Aware they have little chance of getting a PVC job, they are unlikely to apply. The continued monopolisation of PVC posts by academic managers represents a form of social closure that serves to maintain their elite status.